2020
DOI: 10.3389/fcell.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

Human Cardiac Progenitor Cells Enhance Exosome Release and Promote Angiogenesis Under Physoxia

Abstract: Studies on cardiac progenitor cells (CPCs) and their derived exosomes therapeutic potential have demonstrated only modest improvements in cardiac function. Therefore, there is an unmet need to improve the therapeutic efficacy of CPCs and their exosomes to attain clinically relevant improvement in cardiac function. The hypothesis of this project is to assess the therapeutic potential of exosomes derived from human CPCs (hCPCs) cultured under normoxia (21% O 2), physoxia (5% O 2) and hypoxia (1% O 2) conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…This is likely through the secretion of other angiogenic factors by LV CPCs. Previous studies have demonstrated activation of pro-angiogenic platelet endothelial cell adhesion molecule-1 43 and angiopoietin-like 4 44 in CPCs exposed to hypoxia. Although we have not measured these factors in the current study, it is logical to postulate that some of these factors could have been responsible for VEGF-independent angiogenesis in LV CPCs.…”
Section: Discussionmentioning
confidence: 97%
“…This is likely through the secretion of other angiogenic factors by LV CPCs. Previous studies have demonstrated activation of pro-angiogenic platelet endothelial cell adhesion molecule-1 43 and angiopoietin-like 4 44 in CPCs exposed to hypoxia. Although we have not measured these factors in the current study, it is logical to postulate that some of these factors could have been responsible for VEGF-independent angiogenesis in LV CPCs.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, oxygen concentration can also determine EV release. Exosomes isolated from human cardiac progenitor cells had a significantly increase under physoxia conditions (5% O 2 ) compared with normoxia (21% O 2 ) and hypoxia (1% O 2 ) 55 .…”
Section: The Change Of Evs Under Hypoxiamentioning
confidence: 94%
“…A useful example of the hypoxia resistance properties of some exosomes involves those produced by mesenchymal stromal cells (MSCs), which now are seen as superior for therapy compared to their parental cells [ 27 ]. Their unusual properties mean that hypoxia-resistant, MSC-derived exosomes may have an important role in the treatment of diseases featuring hypoxic tissues [ 12 ], such as in myocardial infarction [ 138 , 139 , 140 ], pulmonary hypertension [ 141 , 142 ], thrombotic diseases [ 143 ], and CNS stroke [ 144 , 145 ]. Thus, hypoxia increases the potency of MSC-derived exosomes that are, in general, healing and trophic in a variety of tissue-inflammatory pathologies, particularly acting favorably on the injured vasculature [ 146 , 147 , 148 , 149 , 150 , 151 ], such as ability to treat neonatal hypoxic injury [ 152 ] and also prevent hyperoxia-induced lung responses [ 153 ].…”
Section: Outstanding Properties Of Exosome Evs For Delivery Of Conmentioning
confidence: 99%